SPECTROPHOTOMETRIC CHARACTERIZATION OF RED WINE COLOR FROM THE VINEYARD REGION OF METOHIA - Babincev, Ljiljana; Gurešić, Dejan; Simonović, Ranko (Journal of Agricultural Sciences (Belgrade), 2016)
Five types of red wine produced from the indigenous grape varieties from Metohia Region (vintage 2014) is characterized on the basis of their chromatic properties. The properties of bottled wines: Merlot, Vranac, Prokupac, Cabernet and Game are analyzed. Chromatic characteristics of these wines have been observed four times during the year - spectrophotometer measurements were performed on wines aged 0, 4, 8 and 12 months. Intensity, hue and brilliance of color of these wines are determined (by usual method of Glories). The amount of coloring matter in them is determined by the usual method of Durmishidze and the percentage of polymeric anthocyanins is calculated as well. Wine ageing decreases the color intensity while the color hue value increases. It was also found that contribution of wine color red pigment decreases with wine ageing, while the percentage of yellow pigment in wine increases. The total amount of colored substances in wines studied decreases with wine ageing, while the percentage of polymeric pigments in wine increases. This study presents the methodology for analyses of the chromatic characteristics presented, and explains the origin influence of wine on these properties. On the basis of these correlations the quality of red wine and its authenticity depending on the place of origin can be established.